CSR and family CEO: the moderating role of CEO's age - Meier, Olivier (Journal of business ethics, 2021)
This study examines to what extent different types of CEOs in family firms influence external and internal stakeholder-related CSP as compared to CEOs in nonfamily firms. Linking family CEO and nonfamily CEO with CSR outcomes, we provide evidence that family CEOs are positively associated with both external and internal CSR, whereas nonfamily CEOs within family firms tend to be negatively associated with both external and internal CSR. We show that the incumbent CEO’s age moderates the above relationships, indicating the existence of shifting family priorities and suggesting a tendency toward CSR conformity as the salience of succession concerns increases.